Faktor-Faktor yang Mendasari Pelayanan Komplementer pada Kehamilan - Almira Gitta Novika; Dewi Setyaningsih; Masruroh Masruroh; Redaneya Centaury (Publikasi Penelitian Terapan dan Kebijakan, 2023)
Complementary therapy services are an essential part of health services. So far, most of the approaches used are conventional, even though Indonesia is a country rich in herbal plants that can be used for health. Women are the biggest users of health services with complementary medicine used by pregnant women are massage, herbal medicine, and aromatherapy. Research objective was to determine the supporting factors and inhibiting factors of complementary services in pregnancy by midwives in the Sleman District. This type of research was qualitative with a descriptive approach—data collection techniques using in-depth interviews. The data analysis used in this research was Miles and Huberman's interactive model. Results: Supporting factors in providing complementary pregnancy services by midwives are knowledge, supporting infrastructure, and opportunities. While the inhibiting factors in providing complementary pregnancy services by midwives were time, place, lack of human resources in providing complementary pregnancy services, midwife communication, lack of public awareness, and most midwives had not attended complementary training. It was concluded that field knowledge and supporting advice are critical factors for the success of complementary services in pregnancy.